2014
DOI: 10.1016/j.ridd.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the intellectual profile of children with intellectual vs. learning disability

Abstract: The Version of Scholarly Record of this Article is published in RESEARCH IN AbstractThe WISC-IV was used to compare the intellectual profile of two groups of children, one with specific learning disorders (SLDs), the other with intellectual disabilities (ID), with a view to identifying which of the four main factor indexes and two additional indexes can distinguish between the groups. We collected information on WISC-IV scores for 267 children (M age =10.61[SD=2.51], range 6-16 years, females = 99) with a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 33 publications
10
54
0
4
Order By: Relevance
“…by a general ability index superior to the cognitive proficiency index; Cornoldi et al, 2014;Poletti, 2016). By considering specific subgroups, we aimed to examine whether SLD cases associated with different clinical categories would be characterized by significantly different profiles.…”
Section: )mentioning
confidence: 99%
“…by a general ability index superior to the cognitive proficiency index; Cornoldi et al, 2014;Poletti, 2016). By considering specific subgroups, we aimed to examine whether SLD cases associated with different clinical categories would be characterized by significantly different profiles.…”
Section: )mentioning
confidence: 99%
“…This incomplete overlap between WM and intelligence seems to indicate that the two constructs are distinguishable and not isomorphic (Conway, Kane, & Engle, 2003. The literature also suggests a partial independence between WM and intelligence. For example, children with learning disabilities typically have WM difficulties despite being normally intelligent (e.g., Swanson & Siegel, 2001; see also Cornoldi, Giofrè, Orsini, & Pezzuti, 2014); and children with ADHD may struggle with WM tasks despite revealing a high level of intelligence (Martinussen, Hayden, Hogg-Johnson, Tannock. 2005; see also Cornoldi, Giofrè , Calgaro, & Stupiggia, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The test, and the WISC-IV version in particular, not only affords a measure of general IQ, but also enables us to investigate different aspects of the performance of children with SLD. To give an example, recent studies using the ten core subtests and the classical four-factor structure found the performance of children with SLD strongly impaired in the Working Memory and, to a lesser extent, in the Processing Speed, but not in the Perceptual Reasoning or Verbal Comprehension indexes (Cornoldi, Giofrè, Orsini, & Pezzuti, 2014;De Clercq-Quaegebeur et al, 2010;Poletti, 2014). Such evidence suggests that the intelligence of children with SLD may be organized differently from that of typicallydeveloping children, especially as regards the role of working memory (WM) and processing speed (PS).…”
mentioning
confidence: 99%